2016
DOI: 10.1016/j.molmet.2016.07.007
|View full text |Cite
|
Sign up to set email alerts
|

The changing microbial landscape of Western society: Diet, dwellings and discordance

Abstract: BackgroundThe last 50–100 years has been marked by a sharp rise in so-called “Western-diseases” in those countries that have experienced major industrial advances and shifts towards urbanized living. These diseases include obesity, type 2 diabetes, inflammatory bowel diseases, and food allergies in which chronic dysregulation of metabolic and/or immune processes appear to be involved, and are likely a byproduct of new environmental influences on our ancient genome. What we now appreciate is that this genome co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
56
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 62 publications
1
56
0
3
Order By: Relevance
“…The last two decades have revealed an increasingly important role of the gut microbiome for human health [1], [2], [3]. Differences in intestinal microbiota composition have been uncovered between healthy controls and those suffering from various diseases, including metabolic pathologies such as obesity, the metabolic syndrome and type-2 diabetes mellitus (T2DM) [4], [5], [6].…”
Section: Introductionmentioning
confidence: 99%
“…The last two decades have revealed an increasingly important role of the gut microbiome for human health [1], [2], [3]. Differences in intestinal microbiota composition have been uncovered between healthy controls and those suffering from various diseases, including metabolic pathologies such as obesity, the metabolic syndrome and type-2 diabetes mellitus (T2DM) [4], [5], [6].…”
Section: Introductionmentioning
confidence: 99%
“…When discussing the role of GM in behavior, health, and disease, it is important to pay respect to the intertwined coevolution between humans and our resident microbes. It is suggested that the sharp increase in various disease states over the last 50–100 years (Campell, ; Linneberg et al, ) can be, at least in part, explained by relatively recent dietary and lifestyle changes in the context of human evolution (Broussard & Devkota, ). Currently, humans, particularly those in industrialized countries, are living in an environment to which they have not adaptively evolved (Gluckman, Low, Buklijas, Hanson, & Beedle, ).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, humans, particularly those in industrialized countries, are living in an environment to which they have not adaptively evolved (Gluckman, Low, Buklijas, Hanson, & Beedle, ). An unintended consequence of industrialization, these changes are putting the GM under evolutionary pressure to shift from a previously mutualistic relationship with their human host to a more antagonistic one (Broussard & Devkota, ; Quercia et al, ). This is due to human evolution requiring significantly more time (Uyeda, Hansen, Arnold, & Pienaar, ) compared to single‐celled organisms such as GM that evolve and adapt to environmental and internal states much more rapidly (within as little as 24 hr; David et al, ; Wu et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations